Community transmission of SARS-CoV-2 with B.1.1.7 lineage in Mumbai, India - Shastri, Jayanthi; Yadav, Pragya D.; Agrawal, Sachee; Shete, Anita M.; Nyayanit, Dimpal A.; Parikh, Swapneil; Gomare, Mangala; Sahay, Rima R.; Patil, Deepak Y.; Dudhmal, Manisha; Kadam, Neelam (Journal of microbiology, immunology and infection, 2022)
The B.1.1.7 (Alpha) variant has been detected in Mumbai, India during February 2021. Subsequently, we retrieved 43 sequences from specimens of 51 COVID-19 cases from Mumbai. The sequence analysis revealed that the cases were mainly affected with Alpha variant which suggests its role in community transmission of SARS-CoV-2 in Mumbai, India.